The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12887-021-02924-5
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival granulomatous capillary haemangioma in children: case report and review of the literature

Abstract: Background Granulomatous capillary haemangioma refers to a benign vascular tumour that commonly affects the skin, with occasional involvement of the mucosa. Reports of conjunctival granulomatous capillary haemangioma in children are uncommon. In this article, we present a case of granulomatous capillary haemangioma and a brief review of the relevant literature. Case presentation An 11-year-old girl presented with a conjunctival mass. An excision of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Besides of common patterns as reddish homogeneous areas, yellow‐white scales and dark red scabs as dermoscopic patterns should be paid more attention to when conducting dermoscopic examination for male children with PG. In our study, the pattern of white rail lines was more often observed in patients with longer course of disease (longer than 1 month), which may correspond histologically to the fibrous septa that surround the capillary tufts or lobules 23 . The pattern is actually consistent with the pathological evolution of the disease.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Besides of common patterns as reddish homogeneous areas, yellow‐white scales and dark red scabs as dermoscopic patterns should be paid more attention to when conducting dermoscopic examination for male children with PG. In our study, the pattern of white rail lines was more often observed in patients with longer course of disease (longer than 1 month), which may correspond histologically to the fibrous septa that surround the capillary tufts or lobules 23 . The pattern is actually consistent with the pathological evolution of the disease.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, the pattern of white rail lines was more often observed in patients with longer course of disease (longer than 1 month), which may correspond histologically to the fibrous septa that surround the capillary tufts or lobules. 23 The pattern is actually consistent with the pathological evolution of the disease. That's why it is hardly to see the typical white rail lines in the skin lesions under dermatoscopy in patients with shorter course of disease (less than or equal to 1 month).…”
Section: Discussionsupporting
confidence: 70%
“…Complete excision is preferred in terms of preventing recurrence and obtaining a specimen for histopathological examination [ 17 ]. Surgical excision with thermal cauterization followed by corticosteroid drops was effective in 52 cases of conjunctival granuloma with no recurrence at six months of follow-up [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision with thermal cauterization followed by corticosteroid drops was effective in 52 cases of conjunctival granuloma with no recurrence at six months of follow-up [ 18 ]. In addition, multiple case reports of conjunctival pyogenic granulomas were successfully treated with surgical resection [ 15 , 17 , 19 ]. However, preserving the integrity of the structure is a difficulty in any surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation